Community study to uncover the full spectrum of rheumatic heart disease in Uganda. Issue 1 (1st August 2018) - Scheel, Amy; Ssinabulya, Isaac; Aliku, Twalib; Bradley-Hewitt, Tyler; Clauss, Alexa; Clauss, Sarah; Crawford, Lexi; DeWyer, Alyssa; Donofrio, Mary T; Jacobs, Marni; Klein, Jennifer; Moore, Teresa E; et al.
Abstract : Objective: Estimates of the prevalence of rheumatic heart disease (RHD) in many endemic countries are limited to samples of children attending schools, which generate an incomplete picture of disease burden in communities. The present study conducted household-based RHD screening in a representative community in Gulu district, Uganda. Methods: Members of households identified through a two-stage cluster-sampling approach between the ages of 5 years and 50 years were invited to undergo limited cardiac testing with a handheld echocardiogram to assess for the presence of RHD. Suspicious cases underwent confirmatory echocardiogram with a fully functional machine. Results: Of the 2453 community members screened, 2.45% (95% CI 1.87% to 3.14%) showed echocardiographic evidence of RHD with 1.26% (95% CI 0.860% to 1.79%) having definite RHD. The overall prevalence of RHD among participants <20 years was 2.52% (95% CI 1.78% to 3.45%), with a borderline prevalence of 1.97% (95% CI 1.33% to 2.82%) and a definite prevalence of 0.544% (95% CI 0.235% to 1.07%). Prevalence rates among youth increased with age and peaked in the age group of 16–20 years. The overall adult prevalence (>20 years) of RHD was 2.34% (95% CI 1.49% to 3.49%). The majority of definite cases were mild (81%) and marked by mitral regurgitation and associated morphological valve changes (71%). Conclusion: Our data reveal a high prevalence of undiagnosed RHD within an endemic community and fill a critical gap in RHD epidemiology in African adults.